Wireless power transfer through asymmetric topological edge states in diatomic chains of coupled meta-atoms - Feis, J; Stevens, CJ; Shamonina, E (AIP Publishing, 2020)
We present a different perspective on wireless power transfer by uniting topological edge states, which are robust states on the edge of a material enforced by topological invariants, with magnetoinductive waves on a 1D diatomic chain of magnetically coupled meta-atoms with intracell coupling exceeding intercell coupling. We show that robust edge states that exist in the stop band of the magnetoinductive waves can, in fact, be used for efficient wireless power delivery by relying on coupling via evanescent modes. Advantages in comparison to wireless power delivery via travelling magnetoinductive waves include lower electromagnetic pollution of the space around the wireless power delivery channel due to the evanescent nature of the modes and robustness against perturbations in the system. This study may change the approach to wireless power systems and near-field sensors based on arrays of coupled meta-atoms.